2017
DOI: 10.1103/physrevlett.119.264501
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic Signatures of Stationary Marangoni-Driven Surfactant Transport

Abstract: We experimentally study steady Marangoni-driven surfactant transport on the interface of a deep water layer. Using hydrodynamic measurements, and without using any knowledge of the surfactant physicochemical properties, we show that sodium dodecyl sulphate and Tergitol 15-S-9 introduced in low concentrations result in a flow driven by adsorbed surfactant. At higher surfactant concentration, the flow is dominated by the dissolved surfactant. Using camphoric acid, whose properties are a priori unknown, we demons… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 41 publications
1
29
1
Order By: Relevance
“…In principle, one should consider two fields, the surface and bulk concentrations, which may locally equilibrate, or not, depending on the kinetic of adsorption and desorption. It is interesting to note, though, that in a recent study of steady Marangoni flows induced by a point source [79,83], the case of camphoric acid is better described by the 2D model, suggesting that such a limiting case could be appropriate for our experimental system. (v) Constant flux.…”
Section: Discussionmentioning
confidence: 99%
“…In principle, one should consider two fields, the surface and bulk concentrations, which may locally equilibrate, or not, depending on the kinetic of adsorption and desorption. It is interesting to note, though, that in a recent study of steady Marangoni flows induced by a point source [79,83], the case of camphoric acid is better described by the 2D model, suggesting that such a limiting case could be appropriate for our experimental system. (v) Constant flux.…”
Section: Discussionmentioning
confidence: 99%
“…We assume that pollutants are advected by the velocity field of the fluid while diffusing with a simple non-dimensional diffusion coefficient . Moreover, we assume that no transport occurs from the surface to the bulk of the flow, so that the bulk concentration can be neglected (Bandi et al 2017). In practice, is limited by chemistry considerations; high values of correspond to a highly polluted surface.…”
Section: Modelling Of Interface Pollutionmentioning
confidence: 99%
“…23 Previously, it has been showed that below the cmc, the surfactant flow is controlled by both adsorption and surface gradient. 11 In this study, we used twice cmc to ensure the saturation of the surface layer. Hence, the ST at this concentration was used for temperature analysis.…”
Section: Resultsmentioning
confidence: 99%